Macroeconomic policy reforms and agriculture: towards equitable growth in Zimbabwe - Bautista, Romeo M.; Thomas, Marcelle; Muir-Leresche, Kay; Lofgren, Hans (International Food Policy Research Institute, 2002)
This report investigates the income and equity effects of macroeconomic policy reforms in Zimbabwe, emphasizing linkages between macroeconomic policies and agricultural performance and agriculture's influence on aggregate income and its distribution. Analyses focus on reform of the foreign trade regime, public expenditure, and tax policy, along with the potential benefits of combining these structural changes with various land reform scenarios. The study uses a CGE model that provides a policy simulation laboratory in which exogenous policy changes are analyzed for their economywide income and equity effects. The report highlights the need for policy complementarities in Zimbabwe that can contribute to equitable growth. It should be of interest not only to those concerned with recent economic developments in Zimbabwe but also to those concerned with the broader issues of macroeconomic reform and its ultimate effects." -- Author's Abstract